READER ENGAGEMENT AND INTERPRETIVE FREEDOM THROUGH LITERARY THEORY (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2024)
This paper explores the dynamic relationship between reader engagement and interpretive freedom through the lens of literary theory. It examines how various theoretical frameworks—ranging from formalism to post-structuralism affect the ways in which readers engage with texts, and how these frameworks either constrain or enable interpretive possibilities. By analyzing key literary theories, including reader-response theory, deconstruction, and cultural studies, the paper argues that interpretive freedom is not solely a product of the text itself, but is influenced by the reader's personal, cultural, and ideological contexts. Furthermore, the paper examines the role of the reader in constructing meaning, suggesting that an interactive approach to reading can foster a more fluid, multifaceted understanding of texts. Ultimately, it highlights the importance of balancing interpretive freedom with critical awareness of the theoretical assumptions that shape our reading practices.